Female sexual function after surgical treatment of urinary incontinence - Rabin, Eliane Goldberg (2019)
Introduction: Urinary incontinence is a common problem that can affect the quality of life of women of all ages and can negatively influence the exercise of sexuality. Aim: The aim of this study was to compare sexual function of women before and after surgical treatment for urinary incontinence. Method: The sample consisted of 38 women with urinary incontinence and surgical treatment (Burch or Sling procedure). The Female Sexual Function Index (FSFI) was used to evaluate sexual dysfunction before and after surgical treatment. Results: The mean age of the women in the study was 48 ± 8.8 years, and 58% were 50 years old or younger. By analyzing FSFI, it was observed that the majority of subjects had an overall index of sexual dysfunction (score < 26 points) before surgery. The desire and arousal domains improved significantly after surgery for all women included in the study. It was also observed that women with higher levels of education had more positive results related to desire. Conclusions: In our sample, in general, sexual function improved after surgical treatment of urinary incontinence, regardless of technique used, particularly in the discounter and pain domain. There was a substantial improvement of the sexual function among women who had presented with cystocele. Desire and arousal improved significantly after surgery, very likely due to the improvement of self-esteem after surgery.